Transport and photoresponse properties in Pr0.5Ca0.5CoO3/Nb-SrTiO3 heterostructure. (2nd January 2015) - Zhao, S. G.; Gu, A.; Yan, X. L.; Hao, L. M.; Xie, Y.; Zhang, T.; Jin, K. X.
Abstract: Transport and photoresponse properties of the heterostructure consisting of a Pr0.5 Ca0.5 CoO3 film and a Nb-SrTiO3 substrate were investigated. The Pr0.5 Ca0.5 CoO3 film exhibits semiconducting behavior and the resistances are decreased when irradiated by a 532 nm laser. The rectifying behaviors are observed in the heterostructure. The ideality factors and the diffusion voltages monotonically decrease with increasing the temperature. The photovoltatges of the heterostructure under the irradiation approach the saturation at about . The minority carrier lifetime of is estimated from the time response properties in the falling process of photovoltages. These results reveal that the Pr0.5 Ca0.5 CoO3 heterostructures have great potentials in photoresponse and photoelectric conversion applications.